The Integration of Design Thinking in MSME Digital Transformation in the Platform Economy Era: A Bibliometric Analysis and Systematic Literature Review (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research aims to analyze research trends related to the integration of design thinking in the digital transformation of MSMEs in the platform economy era, identify the main themes that are developing, and formulate a conceptual model that can support the digital transformation of MSMEs in a more integrated manner. The research uses the Systematic Literature Review (SLR) method combined with bibliometric analysis. Data was obtained from scientific articles indexed in relevant international and national databases, then selected based on predetermined inclusion and exclusion criteria. Bibliometric analysis was carried out using the VOSviewer application to map relationships between keywords, publication trends and developments in research themes. The research results show that studies regarding design thinking, digital transformation, and the platform economy are still developing separately and have not been integrated much into one comprehensive conceptual framework. Bibliometric mapping shows the dominance of the themes "Indonesia", "digital transformation", and "design thinking", as well as the emergence of new themes such as QRIS and artificial intelligence in recent publications. Based on a literature synthesis, this research offers a conceptual model of Design Thinking–Driven MSME Transformation that integrates understanding user needs, digital strategy, and utilization of platform ecosystems.